Implementasi Metode Storytelling pada Materi Pengalaman Pribadi untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas III SD - Samsul Arifin; Merryn Istiqommah Putri Hidayat; Reta Novita Sari; Agustina Devita; Nur Wiji Sholikin (IEC: Journal of Educational Innovation, 2026)
This study aims to determine the effect of the storytelling method on students' Indonesian language learning outcomes in the topic of personal experiences among third-grade elementary school students. The topic of personal experiences is an essential component of Indonesian language learning because it helps students develop language skills, express ideas, and improve their speaking and writing abilities. However, based on classroom observations, many students still experienced difficulties in understanding and recounting their personal experiences in a coherent and engaging manner. Therefore, an instructional method that actively engages students in the learning process is needed. The storytelling method was selected because it enables students to understand the learning material through meaningful, engaging, and contextualized stories. This study employed a quantitative approach using a pre-test and post-test research design. The participants consisted of 26 third-grade elementary school students. The research instruments included pre-test and post-test questions. The data were analyzed using IBM SPSS Statistics through normality testing and the Mann–Whitney test. The results indicated that the students' mean score increased from 48.65 on the pre-test to 56.35 on the post-test. However, the Mann–Whitney test revealed a significance value of 0.110 (p > 0.05), indicating that the improvement was not statistically significant. Nevertheless, the storytelling method demonstrated a positive tendency to improve students' learning outcomes in the topic of personal experiences.